PELAKSANAAN PROGRAM COMMUNITY DEVELOPMENT PT. RIAU ANDALAN PULP AND PAPER - Adis Ismala Sari; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Community Development Program is now considered as one of the innovations in improving community welfare, this is carried out by the community of sustainable development activities. In accordance with regional regulation number 6 of 2012 concerning corporate social responsibility in Riau Province, each company must carry out its social responsibilities to the community. This is a lot of companies that do not understand the importance of social responsibility as a role in improving community welfare. But PT. Riau Andalan Pulp and Paper was able to show success in implementing a social responsibility program to get an award in the income generating program that received the community. The purpose of this study was to find out the implementation of the PT.Riau Andalan Pulp and Paper community empowerment program at Kerinci Pangkalan Pelalawan Regency.The type of research used is descriptive qualitative. Data collection is done by interviews, observation and literature studies.The results of the study show that PT. Riau Andalan Pulp and Paper has implemented an optimal community empowerment program. In the implementation of the program, there are still factors that influence it, namely: the lack of community participation, the level of community knowledge on community empowerment programs that are still low.Keywords: Human Development, Business Development, Community Development, Instutional Development